Midterm Outcomes following Acute Repair of Grade III Distal MCL Avulsions in Multiligamentous Knee Injuries - Desai, Vishal S.; Wu, Isabella T.; Camp, Christopher L.; Levy, Bruce A.; Stuart, Michael J.; Krych, Aaron J. (The Journal of Knee Surgery, 2020)
There is limited evidence guiding management of medial collateral ligament (MCL) avulsions or functional disruptions distal to the medial joint line. This study aims to determine outcomes of a series of patients with grade III distal MCL injuries managed with acute surgical repair. Patients with grade III, distal MCL injuries, with or without multiligament involvement were identified. Demographic, clinical examination, and midterm patient-reported outcomes (PRO) data were collected. Clinical follow-up included physical examination and ligamentous stress testing at a minimum of 6 months. PROs included Lysholm's knee scoring scale, Tegner's activity score, and subjective International Knee Documentation Committee (IKDC) scores at minimum of 2 years follow-up. Of the 24 eligible patients, outcomes data were available for 20 (83%). Of the 20 included patients, 16 had a concomitant anterior cruciate ligament (ACL) injury, 3 had ACL and posterior cruciate ligament (PCL) injuries, and 1 had an isolated MCL injury. Mean time from injury to surgery was 5 weeks. At mean clinical follow-up of 20.3 months, all patients showed valgus stability and satisfactory range of motion (ROM). Anteroposterior stability was normal in all but one patient who demonstrated a 2+ posterior drawer but with firm end points. At a mean follow-up of 5.7 years for PROs, mean Lysholm's score was 91.5 (standard deviation [SD] = 12.2), median Tegner's activity score was 7 (range, 4–9), and mean subjective IKDC score was 88.8 (SD: 9.9). The surgical repair of grade III distal MCL injuries delivered satisfactory clinical and functional outcomes. Future comparative studies with larger patient samples are needed.
Keywords: medial collateral ligament; distal avulsion; repair; midterm outcomes; multiligament instability